Sistem Pengelolaan Payroll Dosen Dengan Metode Gross Up ( studi kasus : STMIK bandung) - Apriyanti, Linda; Wijaya, Rena (Jurnal Bangkit Indonesia, 2024)
The lecturer payroll management system using the gross up method is a method for calculating lecturer salaries in which the income tax that must be paid by the lecturer is added to the lecturer's gross salary, so that the amount of income tax that must be paid is the responsibility of the university or institution where the lecturer is located. Work. In its application, the gross up system makes it easier to calculate and pay lecturer salaries because the institution where the lecturer works will bear the costs of the lecturer's income tax. In this case, the institution will calculate the lecturer's income tax first, then add the tax amount to the lecturer's gross salary so that the lecturer receives a net salary which has been calculated and includes income tax costs. The system was designed using UML UML which includes use case diagrams, activity diagrams and sequence diagrams, and was built using Larvel version 10 and for the database using MySQL. It is hoped that with this system the tax burden will decrease and lecturers' take home pay will increase.